DEVELOPMENT ON IMAGING DIAGNOSTIC METHOD AS PREVENTING ACT AGAINST STUNTING IN BREMI VILLAGE KRUCIL DISTRICT PROBOLINGGO REGENCY - Muhaimin; Amilia Kartikasari; Lailatul Muqmiroh; Septyani Prihatiningsih; Rizky Amalia S.; Endah Sekar P.; Riris Medawati (Jurnal Layanan Masyarakat, 2023)
The aims of community service activities is to increase public awareness in monitoring the development of children's growth and development since they are still in the womb through screening methods using diagnostic imaging. This program of proposed community service activities is based on an analysis of the needs of partners and considers the capabilities of the implementing team. The solution that will be provided in this community service activity is by providing training to village health workers (village midwives) on screening methods for early detection of stunting in pregnant women. Routine examinations in pregnant women can help find out whether the growth of the fetus is appropriate for age. In order to avoid stunted fetal growth, pregnant women must not be in a state of malnutrition and must avoid infection during pregnancy so that premature birth does not occur. One of the accurate tests to monitor fetal development is to use ultrasound diagnostic imaging. This community service activity was carried out on September 17 2022 at the Bremi Eco Park, Krucil District, Probolinggo Regency. The form of activity that will be carried out is in the form of counseling related to screening methods using diagnostic imaging modalities to the Bremi village community, especially health cadres as well as stunting screening examinations for pregnant women using Ultrasonography (USG).